The Role of Good Corporate Governance in Preventing Financial Distress - Nurul Fitri Ismayanti (STIEKOP MALANG PRESS, 2026)
Purpose – This study aims to analyze the role of good corporate governance in preventing financial distress through a literature review. Design/methodology/approach – The research method uses a qualitative approach with library research. Data were obtained from scientific journals, books, regulations, and reports from international organizations discussing corporate governance and financial distress. Findings – The results of the study show that the implementation of the principles of transparency, accountability, responsibility, independence, and fairness can improve the effectiveness of supervision, strengthen internal control systems, reduce agency conflicts, improve the quality of decision-making, and improve corporate risk management. Governance mechanisms such as an independent board of commissioners, audit committee, institutional ownership, and internal control systems play an important role in reducing the probability of financial distress. Research limitations/implications – Although many studies have found a negative relationship between GCG and financial distress, empirical results have not been entirely consistent due to differences in industry sectors, company characteristics, and the governance indicators used. Originality/value – These findings reinforce the view that Good Corporate Governance is an important preventive strategy to maintain corporate sustainability.